Сутність та особливості регіону як адміністративно-правової категорії - Герасимчук, Р. В.; Herasymchuk, R. V.; ORCID: https://orcid.org/0000-0003-0490-5045 (Право.ua. - 2021. - № 2. - С. 206-209, 2021)
Розкрито сутнісний зміст поняття регіон, на основі чого запропоновано авторське бачення щодо тлумачення цієї наукової категорії. Відмічено, що в межах регіону відбуваються не тільки юридичні процеси, але також явища природного, етнографічного, культурного, соціального та іншого характеру. Виокремлено ключові особливості регіону як адміністративно-правової категорії.

It is argued that, in the semantic sense, the word “region” is reduced to the spatial characteristics of a part of the earth’s surface. However, in the economic, geographical and historical scientifi c fi elds, it is a special socio-cultural center within which various fi nancial, political, ethnographic and other processes take place. Attention is focused on the fact that not only legal processes take place within the region, but also phenomena of a natural, ethnographic, cultural, social and other nature. In this regard, the region is: fi rst, a legally defi ned part of the territory of our country, namely, the region, the city of Kyiv and Sevastopol and the ARC, which has individual administrative boundaries, its own legal status, economy, and political system; secondly, the socio-cultural center of the state, which has its own culture, history, ethnicity, characteristics and specifi cs of social development, as well as a peculiar mentality; thirdly, a geographical object located within the national border, which is characterized by individual physical and geographical properties, such as relief, climate, features of the landscape and soil, vegetation, animal life, and so on. The following features that characterize a region as an administrative-legal category are highlighted: a) regions determine the structuralterritorial division of state power in Ukraine; b) they have a specifi c construction of the regional management system, which is called “local selfgovernment”; c) act as centers of functioning of many political processes. For example, the activities of the relevant political parties and their representatives are aimed at improving the livelihood of the population and solving problems at the local level related to the economic development of the regions, the formation of a high level of security, the control of life support issues, and so on; d) it is on their basis that the administrative-territorial division of the country into smaller constituent elements, i.e., corresponding districts, is determined; e) regions are the object of a separate direction of state policy - regional.

Раскрыто сущностное содержание понятия регион, на основе чего предложено авторское видение толкования этой научной категории. Отмечено, что в регионе происходят не только юридические процессы, но также явления природного, этнографического, культурного, социального и иного характера. Выделены ключевые особенности региона как административно-правовой категории.
Герасимчук, Р. В. Сутність та особливості регіону як адміністративно-правової категорії / Герасимчук Руслан Володимирович // Право.ua. - 2021. - № 2. - С. 206-209. - DOI: 10.32782/LAW.UA.2021.2.30
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; регіон; region; регион; територія; territory; территория; адміністративно-правова категорія; administrative and legal category; административно-правовая категория; погляди вчених; views of scientists; взгляды ученых; державна політика; state policy; государственная политика; правове регулювання; legal regulation; правовое регулирование